Epidemiological Characteristics of Hand, Foot and Mouth Disease Reinfection in Guangzhou, Southern China from 2012 to 2017 - Xuan Zhong; Hui Wang; Chun Chen; Xiaoni Zou; Tiegang Li (Tehran University of Medical Sciences, 2022)
Background: Hand, foot and mouth disease (HFMD) reinfection is common because of the limited cross-protection from infections of different enterovirus. We aimed to investigate the epidemiological characteristics and its influential factors of HFMD reinfection in Guangzhou, China. Methods: Data on HFMD patients aged ≤5 yr from 2012 to 2017 were extracted from surveillance system. Influential factors of reinfection were assessed using the logistic regression model. Results: Of 369,054 HFMD patients, 11,321 patients (3.07%) were classified as reinfection. The reinfection rate in male was higher than in female (χ2=60.11, P<0.001). The reinfection rate in patients ≤1 yr was 3.86%, which showed a downward trend with age (Z=37.37, Ptrend<0.001). The highest reinfection rate was observed in the scattered children (3.38%), followed by nursery care children and others (χ2=514.75, P<0.001). Besides, higher risk of reinfection was detected among those who were male, lower age group, rural residence and other enteroviruses infection compared with their respective counterparts. Seasonality was illustrated according to the number of reinfections peaked from April to July. Time intervals curves revealed the number of reinfections gradually increased after 13 months from the initial infection. Conclusion: Male ≤4 yr, living rural area, especially those lived scattered and infected with other enteroviruses were more likely to be reinfection.